Vous êtes sur la page 1sur 13

Factoring and Solving

Polynomial Equations

Factor Polynomial Expressions


In the previous lesson, you factored various
polynomial expressions.
Groupi
ng c o
m
Common
Factor

m
factor t
he first on
terms a
n d th en tw o
two ter the last
ms .

Such as:
2
x
x3 2x2 = (x 2)
3
2
x(x

x
3x + 3)
x4 x3 3x2 + 3x =
2
x[x
(x

1)

3(x

1)]
=
Comm
2
on
x(x
3)(x 1)
Factor
=

Solving Polynomial Equations


The expressions on the previous slide are
now equations:
y = x3 2x2 and y = x4 x3 3x2 +3x
To solve these equations, we will be solving
for x when y = 0.

Solve
Let y = 0

y = x3 2x2
0 = x3 2x2
0 = x2(x 2)
x2 = 0 or x 2 = 0
x=0 x=2

Common factor
Separate the factors and set
them equal to zero.
Solve for x

Therefore, the roots are 0 and 2.

Solve
y = x4 x3 3x2 + 3x
0 = x4 x3 3x2 + 3x
0 = x(x3 x2 3x + 3)
0 =x[x2(x 1) 3(x 1)]
0 = x(x 1)(x2 3)

Let y = 0
Common factor
Group

Separate the factors and set


them equal to zero.
Solve for x
x = 0 or x 1 = 0 or x2 3 = 0
x=0
x=1
x= 3
Therefore, the roots are 0, 1 and
1.73

The Quadratic Formula


b b 2 4ac
x
2a

where a 0

For equations in quadratic form: ax2 + bx + c = 0, we can use


the quadratic formula to solve for the roots of the equation.
This equation is normally used when factoring is not an
option.

Using the Quadratic Formula


Solve the following cubic equation:
Can this equation
be to solve for x
We still need
y = x3 + 5x2 9x
factored?here. Can this equation be
0 =YES
x(xit2 can
+ 5x 9)
factored?
factor.
x =common
0
x2 + 5x 9 = 0
No. however,
There are no
two
We can,
use
the quadratic formula.
integers that will multiply
a = 1to -9 andadd
( 5) to
5.
( 5)2 4(1)( 9)
x
b=5

c = -9

(2)(1)

5 61
2
x 6.41, 1.41
x

Remember, the
root 0 came from
an earlier step.

Therefore, the roots are 0, 6.41 and


-1.41.

Factoring Sum or Difference of


Cubes
If you have a sum or difference of cubes such as a3 + b3 or
a3 b3, you can factor by using the following patterns.

Sum of Two Cubes


a 3 b3 (a b)(a 2 ab b 2 )
Difference of Two Cubes
a b (a b)(a ab b )
3

Note: The first and last term are cubed and these are binomials.

Example
Factor x3 + 343.
Note: This is a binomial. Are the first and last terms cubed?
3

x3 x

343 7

a 3 b 3 (a b)(a 2 ab b 2 )
x3 + 343 = (x)3 + (7)3
= ( x + 7 )( x2 - 7x + 49)

Example
Factor 64a4 27a
= a(64a3 27)
Note: Binomial. Is the
first and last terms cubes?
= a( (4a)3 (3)3)

Note: a3 b3 (a b)(a 2 ab b 2 )

= a( 4a - 3)( 16a2 + 12a + 9 )

Factor by Grouping
Some four term polynomials can be factor by grouping.
Example.

Factor 3x3 + 7x2 +12x + 28

Step 1 Pair the terms.


(3 x 3 7 x 2 ) (12 x 28)

Step 2 Factor out common factor from each pair.


x 2 (3x 7) 4(3x 7)
Identical factors
Step 3 Factor out common factor from each term.

(3 x 7)( x 2 4)

Example
Factor 3x3 + 7x2 -12x - 28
Step 1

(3x 3 7 x 2 ) (12 x 28)

Step 2

x 2 (3 x 7) (4)(3x 7)

Step 3

(3x 7)( x 2 4)
(3x 7)( x 2)( x 2)

Note: Subtraction is
the same as adding a
negative

Note: This factor can


be further factored

Solving Polynomial Equations


Solve

x 3 2 x 2 9 x 18

Set equation equal to zero.


x 3 2 x 2 9 x 18 0

Factor.

( x 3 2 x 2 ) ( 9 x 18) 0
x 2 ( x 2) ( 9)( x 2) 0
( x 2 9)( x 2) 0
( x 3)( x 3)( x 2) 0

Set each factor equal to zero and solve.


( x 3) 0
x 3

( x 3) 0
x3

( x 2) 0
x 2